2005
DOI: 10.1242/jcs.02620
|View full text |Cite
|
Sign up to set email alerts
|

NOSTRIN functions as a homotrimeric adaptor protein facilitating internalization of eNOS

Abstract: Intracellular trafficking of endothelial nitric oxide synthase (eNOS) between different compartments is incompletely understood. Recently, we described a novel eNOS-interacting protein, NOSTRIN, which upon overexpression drives eNOS away from the plasma membrane towards intracellular compartments. Sequence similarity of NOSTRIN and pacsins/syndapins suggested a role for NOSTRIN in endocytosis. Accordingly, we show here that NOSTRIN interacts with the large GTPase dynamin and the actin nucleation promoting fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 56 publications
(81 reference statements)
3
70
0
Order By: Relevance
“…In the absence of NOSTRIN, there was hardly any overlap of caveolin-1 or eNOS with dynamin-2-GFP ( Figure 7, E-H). However, in the presence of NOSTRIN, eNOS localization was clearly changed in favor of vesicular and tubular structures (Figure 7, I-L) previously demonstrated to be positive for NOSTRIN (Icking et al, 2005). In these NOSTRIN-expressing cells, eNOS colocalized extensively with dynamin-2-GFP and caveolin-1 ( Figure 7L, inset).…”
Section: Nostrin Recruits Dynamin To Caveolin-positive Structuresmentioning
confidence: 67%
See 4 more Smart Citations
“…In the absence of NOSTRIN, there was hardly any overlap of caveolin-1 or eNOS with dynamin-2-GFP ( Figure 7, E-H). However, in the presence of NOSTRIN, eNOS localization was clearly changed in favor of vesicular and tubular structures (Figure 7, I-L) previously demonstrated to be positive for NOSTRIN (Icking et al, 2005). In these NOSTRIN-expressing cells, eNOS colocalized extensively with dynamin-2-GFP and caveolin-1 ( Figure 7L, inset).…”
Section: Nostrin Recruits Dynamin To Caveolin-positive Structuresmentioning
confidence: 67%
“…Importantly, whereas eNOS interacts with the SH3 domain of NOSTRIN (positions 434 -506), binding of caveolin to NOSTRIN depends on residues 323-434 of NOSTRIN, allowing for formation of a ternary complex of NOSTRIN, caveolin, and eNOS. At present, we do not know the precise stoichiometry of the protein complex but given that caveolin-1 oligomerizes to large complexes of up to 600 kDa (Monier et al, 1995) and that eNOS and NOSTRIN form homodimers and -trimers, respectively (Icking et al, 2005), the resultant macromolecular complex may provide a platform for dynamic recruitment of proteins involved in caveolar function. Previous reports suggested that interaction of eNOS and caveolin may be regulated (Andries et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations